The little black book of online business : 1001 insider resources every business owner needs - Galloway, Paul (Wiley, 2009)
"All in one Resource for Internet marketers: This is the only book where internet marketers in myriad fields and industries can acquire access to an itemized and categorized listing of tools to fuel online business. The Little Black Book of Online Business includes a 65 page directory of the best, proven resources to help you explode your Internet business. It has been touted as "a required resource for anyone doing business on the net", and has been downloaded from his site over 6,000 times since he first made it available."--Publisher's website